Janette Turner Hospital: A Preliminary Bibliography 1973-1988 - Stone, Ron (LiNQ (Literature in North Queensland), 2016)
The following bibliography must be viewed as a preliminary attempt to list works by and about Janette Turner Hospital. For some parts of the bibliography, especially the book reviews and critical material, I have had to rely on secondary sources. Until I am able to examine all of the primary materials, I am unable to indicate the author of each review and to classify them into major or minor reviews. I wish to acknowledge the continuing assistance of Janette Turner Hospital in compiling this bibliography although I take responsibility for any errors it may contain. If any errors or omissions are detected by readers, I should be grateful if they were brought to my attention.